Accuracy of custom-fitted temporomandibular joint alloplastic reconstruction and virtual surgical planning. Issue 8 (August 2019) - Sembronio, S.; Tel, A.; Costa, F.; Isola, M.; Robiony, M.
Abstract: The purpose of this study was to evaluate the accuracy of temporomandibular joint (TMJ) custom-made replacements by means of virtual surgical planning. The authors review 11 TMJ custom-made prostheses made of both mandibular and fossa components. Surgeries were virtually planned and patient-specific devices were designed together with surgical cutting and positional guides. Three-dimensional models for both preoperative planning and postoperative computed tomography scans were generated and overlapped in order to evaluate differences in measurements. Correlation between virtual preoperative and real postoperative prosthesis positioning was described by Lin's coefficient. Results of statistical analysis showed an almost perfect concordance. Wilcoxon's matched-pairs test showed no statistically significant deviation between preoperative virtual surgical planning and postoperative results. Colour map analysis confirmed the correspondence between virtually planned positioning of the devices and postoperative results. All the prostheses were placed with great accuracy. In conclusion, virtual surgical planning, surgical guides and patient-specific devices provide accuracy and precision in surgery for custom-made TMJ replacement.